HUBUNGAN KATA YAHUDI DAN ISRAIL DALAM AL-QUR'AN (Studi Tafsir Al-Azhar Hamka) - Muhammad, Imaduddin; Abror, Indal (UIN Mataram, 2024)
Recently, Israel has become a major topic of public discussion due to the renewed conflict with Palestine that has been ongoing for approximately 76 years. The Qur'an, as the holy book of Islam, mentions the words